Adaptive Control for Joint Module of Bionic Arms. Issue 1 (1st December 2022) - Guo, Yuting; Li, Baojiang; Wang, Haiyan; Bai, Jibo
Abstract: Minimizing the influence of unknown external disturbances while satisfying complex control requirements in daily life is one of the difficulties of bionic arm control. However, the control of modular joints often ignores the dynamic characteristics and coupling relationship of the system, which can not meet the control requirements of a bionic arm prosthesis. In addition, the large vibration caused by unknown interference is not conducive to human-computer interaction. In order to solve this problem, we proposed an adaptive feedback control (AFC) method based on magnetic field-oriented control for the joint module to realize intelligent control of the bionic arm. The disturbance of the joint module is obtained by real-time parameter calculation. At the same time, the controller regulated the output voltage to eliminate the influence of uncertain disturbances. Theoretical analysis and simulation results show that the controller has a good effect on improving the dynamic performance of the joint module system, and maintaining the stability of the system in the interference, satisfying the requirements of bionic arm control.